Avaliação dos impactos ambientais dos tratamentos de resíduos de solventes no instituto de química da universidade de São Paulo - Martins,Cláudia R. (2017)
As the result of research work and teaching, the Instituto de Química da Universidade de São Paulo generates 10,000L/year of used solvent mixtures. Although recovery is usually considered an attractive alternative to incineration, a fundamental question remained unanswered: how to ascertain and compare environmental impacts of distillation of a waste mixture of solvents or its disposal by incineration. To this end, after separation of the components of ten solvent mixtures by distillation, Ecosolvent® software was used to compare, for both alternative methods, the EI99 values for some parameters like mass balance, energy and water consumption, gaseous emissions and transportation to the incinerating facility. Results showed that for nine of such mixtures the EI99 parameters were lower for distillation than for incineration.